2011
DOI: 10.1111/j.1365-2184.2011.00769.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose-specific effects of tumor necrosis factor alpha on osteogenic differentiation of mesenchymal stem cells

Abstract: The binding of TNF-α to its receptors results in the activation of multiple signaling pathways, which actively interact with each other to regulate the differentiation, proliferation, survival and apoptosis of MSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
133
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(148 citation statements)
references
References 33 publications
(45 reference statements)
10
133
1
1
Order By: Relevance
“…The process of bone formation involves a balance between osteoblast and osteoclast activity and the healing of fractures requires a large number of osteoblasts (6). It has been demonstrated that there is a link between osteoclasts and inflammatory cytokines: High numbers of osteoclasts are associated with high numbers of inflammatory cytokines, including TNF-α and IL-1, following bone fracture (7).…”
Section: Introductionmentioning
confidence: 99%
“…The process of bone formation involves a balance between osteoblast and osteoclast activity and the healing of fractures requires a large number of osteoblasts (6). It has been demonstrated that there is a link between osteoclasts and inflammatory cytokines: High numbers of osteoclasts are associated with high numbers of inflammatory cytokines, including TNF-α and IL-1, following bone fracture (7).…”
Section: Introductionmentioning
confidence: 99%
“…Both TNF-and IFN-inhibited MSC osteogenic ability in dose-dependent manner in vitro (180). Interestingly, an in vitro exposure to IFN-augmented TNF--mediated apoptosis of BM MSCs and suppressed their osteogenic differentiation (182,191). The IFN--mediated inhibition of osteogenesis of MSCs was associated with increased expression levels of SMAD-6, a negative controller of bone differentiation (182).…”
Section: Cytokinesmentioning
confidence: 93%
“…In chronic inflammatory milieu, TNF-suppresses the biomarkers of MSC osteogenic differentiation via NF-signalling-dependent mechanism (191). An exposure of mouse…”
Section: Cytokinesmentioning
confidence: 99%
“…Several studies have proven that inflammatory cytokines IFN-g and TNF-a can block the osteogenic differentiation of MSCs [115,116]. TNF-a also works to enhance the expression of Wnt signalling pathway antagonist, Dickkopf-1 (DKK-1) that has an inhibitory effect on the osteoblast formation [117] and inhibits nephronectin, an extracellular matrix protein, which helps the proliferation of osteoblasts [118].…”
Section: The Uncontrolled Immune Cell Response and Defective Bone Heamentioning
confidence: 99%